Comparison of the tuberculin skin test and Quanti-FERON-TB Gold In-Tube (QFT-G) test for the diagnosis of latent tuberculosis infection in dialysis patients - Hamdan Al Jahdali; Anwar E. Ahmed; Hanan H. Balkhy; Salim Baharoon; Fayez F. Al Hejaili; Ali Hajeer; Ziad Memish; Salih Binsalih; Abdullah A. Al Sayyari (Elsevier, 2013)
Summary: Dialysis patients are more likely than the general population to develop active tuberculosis (TB). In these patients, the availability of a highly sensitive and specific test to diagnose latent TB will ensure earlier treatment and decreased progression to active disease. In the current study, the Quanti-FERON-TB Gold In-Tube (QFT-G) test was compared with the tuberculin skin test (TST) for the diagnosis of latent tuberculosis infection (LTBI) among 200 hemodialysis patients and 15 confirmed TB disease cases in a tertiary care center in Saudi Arabia. Among the LTBI cases, 26 (13%) were TST positive, and 65 (32.5%) were positive by the QTF-G test, with an overall agreement between the 2 tests of 75.5% (k = 0.34) being observed. Among the confirmed tuberculosis disease cases, none were positive by TST, and 10 (66.7%) were positive by the QTF-G test, resulting in an overall agreement of 33.3% (k = 0). A comparison between the TST and the QTF-G test was performed based on the sensitivity, specificity, and area under the curve (AUC) obtained for the tests. The QTF-G test was more sensitive and less specific than the TST in predicting the confirmed TB disease cases. When we tested the correspondence of the AUC values between the 2 diagnostic modalities, the obtained p-value was 0.0003. In conclusion, the AUCs of the examined diagnostic modalities are significantly different in predicting LTBI and tuberculosis. Keywords: Tuberculosis (TB), Tuberculin skin test (TST), QTF-G test, Dialysis, Hemodialysis, Chronic renal failure, Latent tuberculosis infection